Enhancer deletions of the SHOX gene as a frequent cause of short stature: the essential role of a 250 kb downstream regulatory domain. Issue 12 (2nd July 2009) - Chen, J; Wildhardt, G; Zhong, Z; Röth, R; Weiss, B; Steinberger, D; Decker, J; Blum, W F; Rappold, G
Abstract : Background: Mutations and deletions of the homeobox transcription factor gene SHOX are known to cause short stature. The authors have analysed SHOX enhancer regions in a large cohort of short stature patients to study the importance of regulatory regions in developmentally relevant genes like SHOX . Methods: The authors tested for the presence of copy number variations in the pseudoautosomal region of the sex chromosomes in 735 individuals with idiopathic short stature and compared the results to 58 cases with Leri–Weill syndrome and 100 normal height controls, using fluorescence in situ hybridisation (FISH), single nucleotide polymorphism (SNP), microsatellites, and multiplex ligand dependent probe amplification (MLPA) analysis. Results: A total of 31/735 (4.2%) microdeletions were identified in the pseudoautosomal region in patients with idiopathic short stature; eight of these microdeletions (8/31; 26%) involved only enhancer sequences residing a considerable distance away from the gene. In 58 Leri–Weill syndrome patients, a total of 29 microdeletions were identified; almost half of these (13/29; 45%) involve enhancer sequences and leave the SHOX gene intact. These deletions were absent in 100 control persons. Conclusion: The authors conclude that enhancer deletions in the SHOX gene region are a relatively frequent cause of growth failure in patients with idiopathic short stature and Leri–Weill syndrome. The data highlights the growing recognition that regulatory sequences are of crucial importance in the genome when diagnosing and understanding the aetiology of disease.